2006
DOI: 10.4102/curationis.v29i2.1082
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve the performance of learners in a nursing college Part II: Issues pertaining to management, attitudes and values

Abstract: This article forms part two of a bigger study that was conducted in a nursing college to explore and describe the reasons for the poor performance of learners. Part one of the study dealt with the issues pertaining to education, while this article (part two) seeks to describe issues pertaining to management, attitudes and values that lead to the poor performance of learners in the nursing college under study.
A qualitative, exploratory and descriptive design that was contextual in nature was employed, an…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Waterson et al (2006) (24) studied strategies to improve the performance of learners in a nursing college, and Last & Fullbrook (2003) (25) study about why do student nurse leave? Suggestion from Adelphi study, both studies supports the present study results and revealed that nurse demonstrators were not sufficiently knowledgeable about the importance of nursing round.…”
Section: Discussionmentioning
confidence: 99%
“…Waterson et al (2006) (24) studied strategies to improve the performance of learners in a nursing college, and Last & Fullbrook (2003) (25) study about why do student nurse leave? Suggestion from Adelphi study, both studies supports the present study results and revealed that nurse demonstrators were not sufficiently knowledgeable about the importance of nursing round.…”
Section: Discussionmentioning
confidence: 99%